Penolakan Peran Dokter Sebagai Eksekutor Sanksi Hukum Kebiri di Indonesia: Perspektif Filsafat Hukum Islam - Abdul Aziz Harahap; Athoillah Islamy (Institut Agama Islam Negeri Kendari, 2021)
Behind the pro-contra polemic of imposing castration legal sanctions for criminals of pedophilia in Indonesia, doctors have a dilemma as a profession that is considered to have medical competence and is worthy of being executors. It is due to the principle of maintaining the safety of human souls and the prohibition of taking action that endangers the lives of others in the code of ethics for the medical profession. The research seeks to present the perspective of Islamic legal philosophy in analyzing the arguments in the Indonesian Doctors Association (IDI) rejection as the executor of the punishment for castration. This research is qualitative in the form of a literature review. This type of legal research is included in the category of philosophical normative Islamic law research using Islamic law principles (qawaid fiqhiyah). This research concludes that the principle of not endangering the safety of others in the medical profession is parallel to the rules of Islamic law (fiqh) which reads al-ḍararu yuzālu (fade must be eliminated). However, the provisions of the fiqh rule are not absolute. It means that under certain conditions, the act of harming someone is allowed in order to create public benefit (al-maslahat al-ammah). Therefore, a doctor who serves as executor in applying the caste penalty for pedophile offenders does not contradict the philosophy of Islamic law.